‘Driving a Micra and working in nasty homes’: a qualitative study of a community nursing service in England - Martina, Sýkorová (2025)
The National Health Service (NHS) is costly to run, which has led to numerous reforms aiming to improve quality of services and reduce costs. One of the more significant NHS reforms was the managerialist reform in the form of New Public Management (NPM) that led to attempts to resolve the inefficiencies of public administration through management. Three decades after the introduction of NPM, NPM policies are believed to have harmed the NHS. Although several studies researched the impact of NPM on nursing, most research focus on nursing managers or nurses working in a hospital setting with a limited knowledge of the impact on NPM on community nursing.